Impact of arteriovenous fistula cannulation on the quality of dialysis. Issue 1 (6th March 2017) - Elias, Michelle; Nnang‐Obada, Erika; Charpentier, Bernard; Durrbach, Antoine; Beaudreuil, Severine
Abstract: Introduction: Adequate hemodialysis directly improves health. Puncturing an arteriovenous fistula (AVF) and the amount of blood recirculation greatly affect the quality of dialysis. Few studies have assessed the method to cannulate a fistula and its influence on efficiency of hemodialysis. Methods: This prospective pilot study included 14 patients with end‐stage renal failure receiving regular intermittent hemodialysis. Patients received three consecutive treatments with both needles directed upstream then three consecutive treatments with the venous needle directed upstream and the arterial needle directed downstream. With both techniques, the distance between the needles was kept constant at 2.5 cm. Recirculation rate and Kt/V ratio were measured during each treatment using thermodilution and a diascan Fresenius generator. Findings: The 14 patients received 84 hemodialysis sessions: i.e., 8 (57.1%) males and 6 (42.8%) females, mean age 62.3 ± 15.57 years. Results showed that mean recirculation rates and Kt/V did not significantly differ between the two techniques. Discussion: Because no significant difference was found between the two techniques, the direction of insertion of needles should be decided upon on a case‐by‐case basis depending on the anatomy of the AVF and the feasibility of the puncture.